Impact of enzyme replacement therapy and hematopoietic stem cell transplantation in patients with Morquio A syndrome - Tomatsu S; Sawamoto K; Alméciga-Díaz CJ; Shimada T; Bober MB; Chinen Y; Yabe H; Montaño AM; Giugliani R; Kubaski F; Yasuda E; Rodríguez-López A; et al. (Dove Medical Press, 2015)
Shunji Tomatsu,1,2 Kazuki Sawamoto,1 Carlos J Alméciga-Díaz,3 Tsutomu Shimada,1 Michael B Bober,1 Yasutsugu Chinen,4 Hiromasa Yabe,5 Adriana M Montaño,6 Roberto Giugliani,7 Francyne Kubaski,1,8 Eriko Yasuda,1 Alexander Rodríguez-López,3 Angela J Espejo-Mojica,3 Oscar F Sánchez,9 Robert W Mason,1 Luis A Barrera,3 William G Mackenzie,1 Tadao Orii2 1Nemours/Alfred I duPont Hospital for Children, Wilmington, DE, USA; 2Department of Pediatrics, Gifu University, Gifu, Japan; 3Institute for the Study of Inborn Errors of Metabolism, School of Sciences, Pontificia Universidad Javeriana, Bogotá, Colombia; 4Department of Pediatrics, Faculty of Medicine, University of the Ryukyus, Okinawa, 5Department of Cell Transplantation and Regenerative Medicine, Tokai University School of Medicine, Isehara, Japan; 6Department of Pediatrics, Saint Louis University, St Louis, MO, USA; 7Medical Genetics Service/HCPA and Department of Genetics/UFRGS, Porto Alegre, Brazil; 8Department of Biological Sciences, University of Delaware, Newark, DE, 9School of Chemical Engineering, Purdue University, West Lafayette, IN, USA Abstract: Patients with mucopolysaccharidosis IVA (MPS IVA) can present with systemic skeletal dysplasia, leading to a need for multiple orthopedic surgical procedures, and often become wheelchair bound in their teenage years. Studies on patients with MPS IVA treated by enzyme replacement therapy (ERT) showed a sharp reduction on urinary keratan sulfate, but only modest improvement based on a 6-minute walk test and no significant improvement on a 3-minute climb-up test and lung function test compared with the placebo group, at least in the short-term. Surgical remnants from ERT-treated patients did not show reduction of storage materials in chondrocytes. The impact of ERT on bone lesions in patients with MPS IVA remains limited. ERT seems to be enhanced in a mouse model of MPS IVA by a novel form of the enzyme tagged with a bone-targeting moiety. The tagged enzyme remained in the circulation much longer than untagged native enzyme and was delivered to and retained in bone. Three-month-old MPS IVA mice treated with 23 weekly infusions of tagged enzyme showed marked clearance of the storage materials in bone, bone marrow, and heart valves. When treatment was initiated at birth, reduction of storage materials in tissues was even greater. These findings indicate that specific targeting of the enzyme to bone at an early stage may improve efficacy of ERT for MPS IVA. Recombinant N-acetylgalactosamine-6-sulfate sulfatase (GALNS) in Escherichia coli BL21 (DE3) (erGALNS) and in the methylotrophic yeast Pichia pastoris (prGALNS) has been produced as an alternative to the conventional production in Chinese hamster ovary cells. Recombinant GALNS produced in microorganisms may help to reduce the high cost of ERT and the introduction of modifications to enhance targeting. Although only a limited number of patients with MPS IVA have been treated with hematopoietic stem cell transplantation (HSCT), beneficial effects have been reported. A wheelchair-bound patient with a severe form of MPS IVA was treated with HSCT at 15 years of age and followed up for 10 years. Radiographs showed that the figures of major and minor trochanter appeared. Loud snoring and apnea disappeared. In all, 1 year after bone marrow transplantation, bone mineral density at L2–L4 was increased from 0.372 g/cm2 to 0.548 g/cm2 and was maintained at a level of 0.48±0.054 for the following 9 years. Pulmonary vital capacity increased approximately 20% from a baseline of 1.08 L to around 1.31 L over the first 2 years and was maintained thereafter. Activity of daily living was improved similar to the normal control group. After bilateral osteotomies, a patient can walk over 400 m using hip–knee–ankle–foot orthoses. This long-term observation of a patient shows that this treatment can produce clinical improvements although bone deformity remained unchanged. In conclusion, ERT is a therapeutic option for MPS IVA patients, and there are some indications that HSCT may be an alternative to treat this disease. However, as neither seems to be a curative therapy, at least for the skeletal dysplasia in MPS IVA patients, new approaches are investigated to enhance efficacy and reduce costs to benefit MPS IVA patients. Keywords: mucopolysaccharidosis IVA, ERT, HSCT, skeletal dysplasia, keratan sulfate